Possibility of Microsimulation Models Calibration – Case Study in the City of Split - Cvitanić, Dražen; Breški, Deana; Lovrić, Ivan (Promet - Traffic&Transportation, 2012)
The paper presents a comparison of the possibility and complexity of the calibration process of two microsimulation models. The first model CORSIM is simple for use while the second named S-Paramics is more complex software. For research purposes, a model of street network with defined geometry (number, width and purpose of lanes) has been made. The volume and distribution of traffic as well as the data about traffic signals were input in the models. Numerous simulations were performed, first with the default parameters of models, and then with the calibrated parameters. Both programs have resulted in very good prediction of the intersection capacity and discharge volumes. However, for the calibration of speed more time and effort have been made in S-Paramics in which the average speed may be higher than the defined free-flow speed. This can present a problem in determining the level of service and comparing the S-Paramics results with other simulation models and analytical method results. On the other hand S-Paramics has greater capabilities than CORSIM (roundabouts modelling, dynamic traffic assignment, opportunity to interact with traffic signals...). Thus, for each specific task, one should carefully choose an appropriate program which would result in necessary and reliable output data with minimum effort and time consumed.